Analisis Penerapan Pendidikan Karakter oleh Guru dalam Pembelajaran Sosiologi pada Peserta Didik Kelas XA di SMA Negeri 5 Pontianak - Tomi Tomi; Sulistyarini Sulistyarini; Thomy Sastra Atmaja (Indo Publishing, 2026)
This research aimed to analyse the implementation of character education done by a sociology teacher during the learning process of Class A Grade 10 in SMA Negeri 5 Pontianak. This research was a qualitative research using descriptive method. The data were collected through observation, interviews, and documentation that involved the sociology teacher and selected students. The results suggested that character education implemented by the teacher during the preliminary activities in the learning process was done through greeting, praying, preparing the class, and late tolerance contract. These series of activities were done to build religiousness, discipline, cooperation, and sense of responsibility in the students’ characters. During the core activities, the teacher used group discussion, assignment, learning material reading, and case study based on social phenomena to instill character values such as responsibility, discipline, collaboration, independent, and cooperation. Lastly, during the closing activities, the teacher gave evaluation, assignment (homework) and praying before dismissing the class, these were done consistently to build characters that were responsible, socially aware, independent, discipline, and religious.